Type 2 Diabetes in Non-Sedentary Workers with Long Working Hours “An Evidence-Based Case Report” - Sofyan, Marwan; Widyahening, Indah Suci; Soemarko, Dewi Sumaryani (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Background: Type 2 diabetes mellitus is a serious threat to public health and the economy. Several reviews suggested that working long hours has a negative effect on health, especially metabolic disorders.Objective: To determine whether long working hours increase the incidence of diabetes mellitus in non-sedentary workers.Methods: A literature search using PubMed, Scopus, and Proquest was conducted based on the clinical question. Selected studies were critically reviewed for their validity using Oxford University’s Center for Evidence-Based Medicine’s etiological study criteria.Result: Three relevant studies were found. A cohort study found that non-clerical workers and shift workers with long working hours had a significantly higher risk of developing diabetes with a Hazard Ratio (HR) of 2.28 (95% Confidence Interval [CI] 1.13-4.82). However, the dominant risk factor that may have influenced the outcomes could not be clearly identified. In contrast, a cross-sectional study found no significant association (p>0.05) between working overtime and diabetes prevalence among field workers. Another cross-sectional study showed that blue-collar workers with long working hours had a higher likelihood of prediabetes with an adjusted Odds Ratio (aOR) of 1.54 (95% CI 1.15-2.06). However, since this is a cross-sectional study, the causal relationship is uncertain. Conclusion: Studies regarding the relationship between long working hours and an increased risk of type 2 diabetes mellitus in non-sedentary workers showed inconsistent and unclear results. Further evaluation is still needed to find more evidence on the health effects of long working hours on workers.